Changes in brain metabolite levels across childhood - Meaghan V. Perdue; Marilena M. DeMayo; Tiffany K. Bell; Elodie Boudes; Mercedes Bagshawe; Ashley D. Harris; Catherine Lebel (NeuroImage, 2023)
Metabolites play important roles in brain development and their levels change rapidly in the prenatal period and during infancy. Metabolite levels are thought to stabilize during childhood, but the development of neurochemistry across early-middle childhood remains understudied. We examined the developmental changes of key metabolites (total N-acetylaspartate, tNAA; total choline, tCho; total creatine, tCr; glutamate+glutamine, Glx; and myo-inositol, mI) using short echo-time magnetic resonance spectroscopy (MRS) in the anterior cingulate cortex (ACC) and the left temporo-parietal cortex (LTP) using a mixed cross-sectional/longitudinal design in children aged 2–11 years (ACC: N = 101 children, 112 observations; LTP: N = 95 children, 318 observations). We found that tNAA increased with age in both regions, while tCho decreased with age in both regions. tCr increased with age in the LTP only. Glx did not show linear age effects in either region, but a follow-up analysis in participants with ≥3 datapoints in the LTP revealed a quadratic effect of age following an inverted U-shape. These substantial changes in neurochemistry throughout childhood likely underlie various processes of structural and functional brain development.